A Class of Coquasitriangular Hopf Group Algebras. Issue 1 (2nd January 2016) - Chen, Q.-G.; Wang, D.-G.
Abstract : This article is devoted to constructing a class of coquasitriangular Hopf group algebras. First, we introduce the notion of group unified product. Then we prove the classification theorem for group unified products and discuss the sufficient and necessary conditions to make the group unified product to be a coquasitriangular Hopf group-algebra. Finally, some applications of the main results are considered.